The Composition of Public Expenditure in Central and Eastern European Countries – a Comparative Analysis - Mikołajczyk, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The recent economic crisis and a search for instruments to overcome its consequences have revived the discussion on the effectiveness of public fiscal intervention on economic growth. The nature and persistence of such interventions have been the subject of numerous studies, which take into account not only the size, but also the financing and composition of public expenditures. The aim of this paper is to compare the size and the structure of public spending in Central and Eastern European countries, stressing their growth-stimulating impact on the economy. The results support the main research hypothesis – that is, the differences in public spending composition in CEE countries are significant and persistent, reflecting the needs of individual fiscal policy. The empirical analysis is based on functional classification of public expenditures for the period 2002–2014 while the main research methods are comparative analysis and panel regressions.